Initial maximum push-rim propulsion and sprint performance in elite wheelchair rugby players - Garcia-Fresneda, A.; Carmona, G.; Padullés, X.; Nuell, S.; Padullés, J. M.; Cadefau, J. A.; Iturricastillo, A. (The Journal of Strength and Conditioning Research, 2019)
Wheelchair rugby (WR) is an increasingly popular Paralympic sport; however, the evidence base supporting the validity and reliability of field tests to assess the physical condition of WR players is in its infancy. Therefore, here, we aimed to evaluate the intrasession reliability of the initial maximum push-rim propulsion (IMPRP) test and the sprint test, and to determine the relationships between IMPRP mechanical outputs and sprint performance variables. We studied 16 Spanish WR players (aged 33 ± 9 years). The maximum single wheelchair push from a stationary position and the sprint performance (i.e., times for 3, 5, and 12 m, and the maximum velocity) of elite WR players were measured in this study. The intraclass correlation coefficient, coefficient of variation, and standard error of measurement for IMPRP variables were >0.85, <10.6%, and <16.76, respectively; the corresponding values for a linear sprint were >0.97, <3.50%, and <0.15. In relation to IMPRP mechanical outputs (i.e., acceleration, maximum acceleration, force, maximum force, power, and maximum power) and sprint performance (i.e., times for 3, 5, and 12 m, and the maximum velocity), significant and large associations were observed in the WR players (r ± confidence limit = -0.78 ± 0.17 to -0.90 ± 0.11; 0/0/100, most likely; R 2 = 0.613-0.812; p < 0.001). These tests provide simple and reliable methods for obtaining accurate mechanical pushing capacities and sprint performances of WR competitors (the 61.4-80.1% variance in sprint performance was explained by the IMPRP variables). These relationships indicate a need to implement specific strength exercises in WR players with the aim of improving the IMPRP and therefore improving sprint capacity.